PENYUSUNAN BASIS DATA SPASIAL SUMBERDAYA AIR MELALUI PARTISIPASI MASYARAKAT (Studi Kasus di Desa Kepuharjo Kecamatan Cangkringan Kabupaten Sleman Provinsi Daerah Istimewa Yogyakarta) - Widayani, Prima (Jurnal Pendidikan Geografi Gea, 2011)
The preparation of spatial database of water resources in the village of Kepuharjo Cangkringan Sleman District implemented through local community empowerment. The objective is to assess the potential and utilization of existing surface water resources in the village of Kepuharjo, District Cangkringan based database of water resource potential. Based on results of the discussion, data collection, field survey and data analysis conducted jointly with local communities showed that rain water and stream water that flowed through the pipe from the spring Bebeng and Kalikuning become the main surface water source Kepuharjo Village residents. Surface water potential is very high especially in the rainy season and has not been used optimally and in August and September the village of Kepuharjo experiencing critical water.Â Keywords : database, water resources, community empowerment.